A Catalog of Natural Products Occurring in Watermelon—Citrullus lanatus - Sorokina, Maria; McCaffrey, Kira S.; Deaton, Erin E.; Ma, Guoying; Ordovás, José M.; Perkins-Veazie, Penelope M.; Steinbeck, Christoph; Levi, Amnon; Parnell, Laurence D. (Frontiers in Nutrition, 2021)
Sweet dessert watermelon (Citrullus lanatus) is one of the most important vegetable crops consumed throughout the world. The chemical composition of watermelon provides both high nutritional value and various health benefits. The present manuscript introduces a catalog of 1679 small molecules occurring in the watermelon and their cheminformatics analysis for diverse features. In this catalog, the phytochemicals are associated with the literature describing their presence in the watermelon plant, and when possible, concentration values in various plant parts (flesh, seeds, leaves, roots, rind). Also cataloged are the chemical classes, molecular weight and formula, chemical structure, and certain physical and chemical properties for each phytochemical. In our view, knowing precisely what is in what we eat, as this catalog does for one fruit, supports both the rationale for certain controlled feeding studies in the field of precision nutrition, and plant breeding efforts for the development of new varieties.